Development of a framework for identifying and measuring collective control as a social determinant of health: findings from an evaluation of a natural policy experiment in empowerment. (13th November 2015) - Ponsford, Ruth; Collins, Michelle; Egan, Matt; Lewis, Sue; Orton, Lois; Salway, Sarah; Townsend, Anne; Halliday, Emma; Whitehead, Margaret; Popay, Jennie
Abstract: Background: Interventions to develop community-level empowerment and participation are advocated within public health strategies that emphasise the importance of control as a social determinant of health. Approaches to defining and measuring collective control, however, are limited. We developed and applied a contextually specific framework for identifying the emergence of collective control in the early stage of a UK area-based community empowerment initiative. Methods: Existing conceptualisations of collective control were used as a basis for development of a logic model, and then framework, for identifying emergent markers of control at the level of intracapability, intercapability, and extra group action. The concepts of power within, power to, and power with were used as overarching categories under which markers of collective control capability and action were identified. The framework was applied to qualitative data generated by our team for this primary analysis from in-depth case studies carried out in ten intervention neighbourhoods in England. Data included contextual area information, 150 interviews, ethnographic observation, participatory group exercises, and the review of 30 local intervention plans. Data were coded in NVivo (version 10) with a predefined thematic framework. Narrative memos were developed and compared and contrasted within and across sites. Ethics approval for the study was awarded by Lancaster University on behalf of Liverpool and Lancaster Universities Collaboration for Public Health Research, and by each individual research institution. Findings: Application of the framework showed that collective control manifested in different ways and to varying degrees across field sites. We observed the emergence of new forms of group organising and decision making; the development of collective efficacy and linkages with other organisations; and the beginnings of community action taking place. The emergence of collective control was shaped by existing relationships between residents and histories with local organisations, as well as through features of the intervention itself, such as the provision of tailored support from national organisations. The processes of developing collective control for those involved were unstable, subject to struggle, and part of a continuing, dynamic, nonlinear process. Interpretation: The conceptual framework helped identify shifts in collective control capability emergent within and between community groups leading to group action, as a result of the introduction of the intervention. These shifts were nevertheless precarious and temporal, suggesting a need for approaches that capture complex collective empowerment processes in flux. Funding: This research was supported by the National Institute of Health Research (NIHR) School for Public Health Research.